P24 A retrospective study exploring GAP index as a predictor of mortality in patients with combined pulmonary fibrosis and emphysema. (11th November 2022) - Alsomali, H; Funston, W; Wiscombe, S; Simpson, J; Ward, C; Forrest, I
Abstract : Introduction: Combined pulmonary fibrosis and emphysema (CPFE) is a distinct clinical condition characterised by coexisting fibrosis and emphysema. The widely used GAP index and staging system in patients with Idiopathic Pulmonary Fibrosis (IPF) has shown prognostic capability. There is a need to identify prognostic tools in CPFE patients. Aims: Explore GAP index as a prognostic tool in CPFE. Methods: Five year retrospective study of regional Interstitial Lung Diseases clinic database with 3063 patients with ILD. GAP stage was calculated with G for Gender, A for Age, and P for lung Physiology; percentage predicted Forced Vital Capacity (FVC%) and percentage predicted Diffusion Capacity of the lungs for Carbon Monoxide (DLCO%). Modified GAP (mGAP) consisted of Gender, Age, and FVC. Results: 149 CPFE patients were included. Ninety-three (62.4%) had IPF subtype of CPFE, 44 (29.6%) non-IPF CPFE, and 12 (8.1%) missing data. Patients with IPF-CPFE had a median survival time of 2.8 yr while Non-IPF CPFE had median survival of 4.6 yr. Kaplan-Meier analysis showed that in the IPF-CPFE both the GAP and the mGAP stage were significant predictors of mortality with p-value of 0.012 and 0.027 respectively ( figure 1 ). In the smaller non-IPF CPFE group, GAP and mGAP did not predict mortality. Conclusion: GAP index and mGAP were significant predictors of mortality in patients with IPF-CPFE and further study of registry data would be useful.